Blantyre Mission and the Making of Modern Malawi - Ross, Andrew (Andrew C.) (Luviri reprints, 2018)
When a thousand leading members of the Nyasaland African Congress were detained under the emergency regulations imposed by the Federation government in 1959, the Presbyterian chaplains who ministered to them at Kanchedza Camp in Limbe were the late Rev Jonathan Sangaya and Rev Andrew C. Ross. They soon discovered that around 700 of the thousand men were members of the Church of Central African Presbyterian. This raised a question in the mind of the recently arrived Scottish missionary: how may we account historically for the fact that so many national leaders were Presbyterians? The quest to answer that question led him to produce the thorough examination of the foundation and early history of the Blantyre Mission of the Church of Scotland which is found in this book. Written in the mid-1960s, it remains today an indispensable work of reference for understanding the history of both church and nation in Malawi.